Evaluation of a Caries Detecting Software System - Aldous DDS, MS, Jay A.; Lowder DDS, Gary; Boseman DDS, Jerald (Odovtos International Journal of Dental Sciences, 2017)
The diagnostic accuracy of caries detecting software that assesses density in digital radiographs was questioned. Analysis of radiographs of extracted teeth using Logicon revealed a deviation in specificity for caries from visual examination of the teeth as well as from their radiographic images. Subsequent preparation of teeth similar to a clinical preparation for a restoration revealed a marked deviation from the Logicon analysis. Radiographic interpretation of early caries and resultant treatment decisions are a multifaceted complex process that is not simplified by desired but unreliable current computerized technique.